IMPROVEMENT OF MATHEMATICS LEARNING OUTCOMES THROUGH TALKING STICK LEARNING METHOD (CASE STUDY: SD NEGERI 1 KALIWUNGU) - Yanuarto, Wanda Nugroho (JLCEdu (Journal of Learning and Character Education), 2021)
This research focuses more on learning based on the 2013 curriculum at the basic unit level. The type of research that will be conducted is collaborative Class Action Research (PTK). The data collection techniques in this study were conducted by (1) observations, (2) tests, and (3) field records. Data analysis techniques in this study using qualitative and quantitative data analysis techniques. Based on the results of the study, teacher activity in each cycle has increased and has achieved the success of established indicators. Judging from the learning outcomes students have also improved and have achieved the success of the indicators set. The obstacles that arise during the learning activities in cycle I and cycle II can be overcome well by finding the right solution/problem solving.